The Poetics of Making Kin: Review of David Farrier, Anthropocene Poetics. Deep Time, Sacrifice Zones, and Extinction - Moe, Aaron (Humanimalia, 2020)
David Farrier, Anthropocene Poetics. Deep Time, Sacrifice Zones, and Extinction. Minneapolis: University of Minnesota Press, 2019. 184 pp. 92.00 (hb); 23.00 (pb).